Transcriptomic and sugar metabolic analysis reveals molecular mechanisms of peach gummosis in response to Neofusicoccum parvum infection - Zhang, Yang; Liu, Yong; Gan, Zhimeng; Du, Wei; Ai, Xiaoyan; Zhu, Wei; Wang, Huiliang; Wang, Furong; Gong, Linzhong; He, Huaping (Frontiers in Plant Science, 2024)
Peach gummosis, a devastating disease caused by Neofusicoccum parvum, significantly shortens peach tree lifespan and reduces the yield of peach trees. Despite its impact, the molecular mechanism underlying this disease remains largely unexplored. In this study, we used RNA-seq, sugar metabolism measurements, and an integrated transcriptional and metabolomic analysis to uncover the molecular events driving peach gummosis. Our results revealed that N. parvum infection drastically altered the transcripts of cell wall degradation-related genes, the log2Fold change in the transcript level of Prupe.1G088900 encoding xyloglucan endotransglycosylase decreased 2.6-fold, while Prupe.6G075100 encoding expansin increased by 2.58-fold at 12 hpi under N. parvum stress. Additionally, sugar content analysis revealed an increase in maltose, sucrose, L-rhamnose, and inositol levels in the early stages of infection, while D-galactose, D-glucose, D-fructose consistently declined as gummosis progressed. Key genes related to cell wall degradation and starch degradation, as well as UDP-sugar biosynthesis, were significantly upregulated in response to N. parvum. These findings suggest that N. parvum manipulates cell wall degradation and UDP-sugar-related genes to invade peach shoot cells, ultimately triggering gum secretion. Furthermore, weighted gene co-expression network analysis (WGCNA) identified two transcription factors, ERF027 and bZIP9, as central regulators in the downregulated and upregulated modules, respectively. Overall, this study enhances our understanding of the physiological and molecular responses of peach trees to N. parvum infection and provide valuable insights into the mechanisms of peach defense against biotic stresses.